2003
DOI: 10.1046/j.1468-1293.2003.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term assessment of neuropsychiatric adverse reactions associated with efavirenz

Abstract: The Sensio study objectives were to assess the outcome of neuropsychiatric adverse reactions (NPAR) that develop after initiation of efavirenz (EFV) therapy, to ascertain the late NPAR after a 3-month treatment period, to evaluate the impact of NPAR on patients' quality of life (QoL) in a real-life population. MethodsDuring a 6-month period, consecutive HIV-infected adult outpatients receiving an ongoing EFV therapy for at least 3 months were asked to ®ll in a speci®cally designed self-administered questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 14 publications
(17 reference statements)
5
92
1
Order By: Relevance
“…The association of efavirenz use with depression or suicide remains controversial [17][18][19][20]. Unfortunately, investigations attempting to address this issue have been either cross-sectional studies or clinical trials with a relatively short follow-up period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of efavirenz use with depression or suicide remains controversial [17][18][19][20]. Unfortunately, investigations attempting to address this issue have been either cross-sectional studies or clinical trials with a relatively short follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…Efavirenz induces depressive-like behaviour and increases stress response in rats [13], and treatment with this drug is often associated with acute central nervous system (CNS) adverse reactions, including insomnia, dizziness and vivid dreams [14,15]. Although these symptoms generally resolve after a few weeks of efavirenz use, a minority of patients may show longer term neuropsychiatric problems [14][15][16].The association of efavirenz use with depression or suicide remains controversial [17][18][19][20]. Unfortunately, investigations attempting to address this issue have been either cross-sectional studies or clinical trials with a relatively short follow-up period.…”
mentioning
confidence: 99%
“…This happens in about 50% of HIV patients and this prevalence decreases to 23% within 3 months. However, the disorders subside after 6 months of therapy [14,22,23]. Efavirenz is not recommended during pregnancy because it can cause hyperlipidemia and liver toxicity.…”
Section: Classes Of Arvs and Their Adverse Effectsmentioning
confidence: 99%
“…3,4,5 Commonly reported side effects include dizziness, insomnia, headache, abnormal dreams and impaired concentration. 4,6,7 These side effects tend to occur within the first few weeks of treatment and spontaneously resolve within that time.…”
Section: Introductionmentioning
confidence: 99%
“…3 It has also been shown that these side effects may persist longer than a few weeks after the initiation of efavirenz. 5 They may in fact persist for up to 2 years and this may influence the long-term adherence to efavirenz. 8,9 The plasma levels of efavirenz as well as genetic polymorphisms in certain populations are thought to be the cause of these neuropsychiatric side effects.…”
Section: Introductionmentioning
confidence: 99%